The weapon - Poyer, David (Poyer, David. Tales of the modern Navy., 2008)
Struggling to obtain the plans for a new Russian nuclear warhead, Navy commander Dan Lenson and his team are betrayed and barely escape with their lives, a situation that prompts an even more dangerous attempt to steal the weapon off of an Iranian submarine.